Nutrition research concepts and applications - Drummond, Karen Eich; Cooke, Natalie K.; Goodell, L. Suzanne; Murphy-Reyes, Alison; Stage, Virginia C. (Burlington, MA Jones & Bartlett Learning, 2023)
"Nutrition Research: Concepts and Applications assists students in developing the skills necessary to become knowledgeable consumers of research, conduct and document research projects, and use research findings in the classroom and in supervised practice. Nutrition Research makes research articles approachable and understandable so students can feel confident reading and interpreting not just primary research, but also narrative and systematic reviews. In turn, this text also helps students understand and access practice guidelines to enable their participation in evidence-based nutrition and dietetics practice"--
Includes bibliographical references and index.
Keywords: Nutrition -- Research